The Role and Function of Homeroom Teachers in Overcoming Burnout Study - Millatul Maftuhah; Mohammad Firdaus (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Study burnout is a learning disorder caused by both physical and psychological fatigue or an overload of assignments given at school. The problems raised in this research are described in three focuses, namely: How does burnout occur during the study of female students in the 3rd grade of Intensive TMI Putri Al-Amien Prenduan, What is the role of the homeroom teacher in overcoming burnout in the study of female students in the 3rd grade of Intensive TMI Putri Al-Amien Prenduan, What are the guardian's obstacles class in overcoming burnout study of female students in class 3 Intensive TMI Putri Al-Amien Prenduan. This research uses a qualitative case study approach. Data sources were obtained from homeroom teachers, teachers, academics and female students. The data collection methods used were observation, interviews and documentation. Data analysis is carried out by reducing data, presenting data, and drawing conclusions. Meanwhile, the technique used to check the validity of the data is technical triangulation. The results of this research are the burnout study that occurs in Intensive Class 3 female students caused by two factors, namely internal and external factors of the child. In this case, the homeroom teacher plays a very active role in overcoming this. The methods used by the homeroom teacher include providing motivation and positive advice, warning, giving rewards, providing adequate rest time for their children and controlling the behavior of female students. The obstacles in overcoming them are internal and external factors.